Optimalisasi Seni Hadroh sebagai Media Pemberdayaan Masyarakat di Dukuh Ngrogung Desa Ngebel Kecamatan Ngebel Ponorogo - Aliffatun Aliffatun; Moh Masduki (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The community of Ngrogung Hamlet, Ngebel Village, possesses rich cultural and religious traditions, one of which is reflected in the practice of hadroh. However, this art form remains limited to the internal circle of youth and has yet to grow as a medium of da’wah and community empowerment. This condition highlights the need for optimization strategies so that hadroh not only serves as religious entertainment but also as a platform for strengthening spirituality, fostering social cohesion, and preserving local cultural identity. This community service aims to empower local residents through hadroh by engaging youth, religious leaders, and the wider community, thereby fostering collective ownership and enhancing the confidence of hadroh groups. The method applied is Asset Based Community Development (ABCD), which includes appreciative inquiry, community mapping, priority setting, individual asset mapping, and local financial circulation analysis. Through this approach, the community’s social, cultural, and economic assets can be identified and optimized. The results show that hadroh is not merely a routine art activity but also functions as a medium of da’wah, religious entertainment, and a cultural identity marker of the Ponorogo community.